Is meta-analysis the "top of the evidence pyramid" in cardiology? - S. Yu. Martsevich (Кардиоваскулярная терапия и профилактика)
The author comments on the significance and place of meta-analyses in modern evidence-based medicine, primarily in cardiology. The history of meta-analyses is briefly described. The main limitations of meta-analyses are reviewed. Examples are given where meta-analyses on the same problem had directly opposite results. The importance of meta-analyses in identifying side effects of drugs is discussed. The possibility of manipulating the results of meta-analyses is demonstrated. The significance of meta-analyses is currently being assessed through the example of the coronavirus pandemic, when different meta-analyses assessed the effectiveness and safety of the same drugs differently.The author concludes that meta-analyses should be excluded from level I evidence and given a more modest role in the hierarchy of evidence.